Acute invasive fungal rhinosinusitis: Molecular identification and update in management of frozen section biopsy. (October 2021) - Shamsaei, Sina; Falahati, Mehraban; Farahyar, Shirin; Raiesi, Omid; Haghighi, Leila; Eraghiye Farahani, Hamed; Akhavan, Asghar; Shamsaie, Alireza; Yarahmadi, Mohammad; Keymaram, Mahyar
Abstract: The clinical diagnosis of Acute Invasive Fungal Rhinosinusitis (AIFRS) is technically difficult because it presents with non-exclusive and nonspecific clinical symptoms. Laboratory confirmation (usually via histopathologic techniques such as formalin-fixed paraffin-embedded (FFPE)) is necessary but it is time-consuming, despite the urgent need for timely diagnosis of AIFRS for effective management. This study aimed to investigate the sensitivity and specificity of the GMS frozen-section biopsy in the diagnosis of AIFRS and compare the same with that of different tissue staining methods to provide valid decision-grounds that may guide clinicians in prompt diagnosis of acute fungal invasive rhinosinusitis. A cross-sectional study was conducted in the Medical Mycology Laboratory, Faculty of Medicine, Iran University of Medical Sciences between 2018 and 2020 on 200 patients with suspected AIFRS referred to Baqiyatallah and Imam Khomeini Hospital, Tehran. All patients were subjected to diagnostic nasal endoscopy and computed tomography (CT) scan of paranasal sinuses. Magnetic resonance imaging (MRI) was done in cases of suspected intracranial extension. After screening by routine mycological examination, the diagnosis was confirmed using complementary molecular methods. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the frozen-section biopsy were also compared with FFPE. Of the 200 suspect patients, 47 cases (23.5%) met the criteria for AIFRS. Species of the genus Aspergillus were the predominant 27 (57.4%) followed by Mucorales species 10 (21.3%), and Fusarium spp 3 (6.4%). Also, 3 cases (6.4%) of co-infection due to Aspergillus/Rhizopus were reported. The accuracy, sensitivity, specificity, PPV, and NPV of frozen section assessments were 99.5%, 97.9%, 100%, 100% and 99.3%, respectively. For GMS frozen-section alone, sensitivity, specificity, NPV, and PPV was 100%. Overall, the calculated accuracy of FFPE was 98.5%, sensitivity was 94%, specificity was 100%, PPV was 100%, and NPV was 98.1%. Examination of the frozen-section biopsy is a highly predictive tool for a rapid and effective diagnosis of patients with suspected AIFRS. We observed that GMS frozen-section is a fast and reliable exam to confirm the diagnosis of fungal invasion, with good accuracy, sensitivity, and specificity compared to the gold-standard FFPE biopsy. Highlights: This 3-year-long study was conducted on 200 patients with suspected AIFRS at two major hospitals in Tehran, Iran. Frozen-section biopsy was a highly predictive tool for a rapid and effective diagnosis of patients with suspected AIFRS. GMS-FSB was a reliable exam to confirm the diagnosis of fungal invasion, with good accuracy, sensitivity, and specificity. 74.4%, 65.9%, 100%, and 100% of proven patients were positive for fungi by microscopic, culture, histopathology, and PCR. Aspergillus spp remains the predominant cause of AIFRS.